2011
DOI: 10.1093/ndt/gfr338
|View full text |Cite
|
Sign up to set email alerts
|

Is N-terminal probrain-type natriuretic peptide a clinically useful biomarker of volume overload in peritoneal dialysis patients?

Abstract: In this cross-sectional study, although NTproBNP was associated with residual renal function, cardiac hypertrophy, volume overload and inflammation on simple univariate analysis, on further examination NTproBNP was predominantly affected by factors associated with volume overload, and these results require confirmation in a prospective study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 21 publications
3
46
0
Order By: Relevance
“…Our cohort was a group of stable outpatient attenders, with median C-reactive protein concentration in the normal reference range, and this may account for the loss of effect of serum C-reactive protein and albumin compared to other studies [24], as the greatest effect on BNP comes from studies following hospital admissions in haemodialysis patients admitted with acute illnesses [25]. However, the strongest association was with post-dialysis ECW/TBW, although there were also other associations with post-dialysis haemoglobin, ultrafiltration rate, and mean arterial blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Our cohort was a group of stable outpatient attenders, with median C-reactive protein concentration in the normal reference range, and this may account for the loss of effect of serum C-reactive protein and albumin compared to other studies [24], as the greatest effect on BNP comes from studies following hospital admissions in haemodialysis patients admitted with acute illnesses [25]. However, the strongest association was with post-dialysis ECW/TBW, although there were also other associations with post-dialysis haemoglobin, ultrafiltration rate, and mean arterial blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, FIGURE 2 presents the Kaplan-Meier curves plotted for the subgroups according to changes in NT-proBNP levels, which were strongly in favor of improved survival in the "decrease" and "stable low" groups. The multivariate Cox proportional hazard regression analysis revealed Papakrivopoulou et al, 24 and Yilmaz et al 26 found substantial correlations between natriuretic peptides and blood pressure. In our study, apart from OH, NT-proBNP was also associated with PRDD, which is not surprising because residual renal function strongly affects NT-proBNP clearance.…”
Section: Discussionmentioning
confidence: 95%
“…These findings are, at least partially, in line with other studies. 20,24,25,31,32 On the other hand, Booth et al 21 was able to connect log NT-proBNP with ultrafiltration rate, whereas Nongnuch et al, …”
Section: -32mentioning
confidence: 99%
See 1 more Smart Citation
“…8 Besides clinical findings (blood pressure, presence of edema, and weight gain), echocardiography, Dual Energy X-ray Absorptiometry (DEXA), direct measurement of extracellular and total body water (TBW), brain natriuretic peptide (BNP) has been used for the determination of hydration status. 9 None of these methods are perfect, each having either clinical or financial limitations. Clinical findings may be misleading as vascular stiffness and cardiac dysfunction may confuse the status by affecting blood pressure.…”
Section: Introductionmentioning
confidence: 99%